2021
DOI: 10.2147/ijgm.s339998
|View full text |Cite
|
Sign up to set email alerts
|

More Aggressive Cancer Behaviour in Thyroid Cancer Patients in the Post-COVID-19 Pandemic Era: A Retrospective Study

Abstract: Many thyroid cancer patients have suffered from treatment delays caused by the coronavirus disease 2019 pandemic. Although there have been many reviews, recommendations, or clinical experiences, clinical evidence that evaluates patient disease status is lacking. The aim of our research was to evaluate thyroid cancer behaviour in the post-COVID-19 era. Patients and Methods: A retrospective study was conducted and thyroid cancer patient data from February 1, 2017 to September 15, 2020 were pooled for analysis. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…It has previously been reported that this changing paradigm did not affect the rate of postoperative complications [14]. Our study documented a slight increase in baseline risk stratification for patients who underwent thyroid surgery after the COVID-19 lockdown, consistent with reports from China, another country hit early by the pandemic [17], though this effect was less marked in our cohort. However, short-term outcomes, evaluated as the early response to initial treatment, were not negatively impacted by the delay.…”
supporting
confidence: 88%
“…It has previously been reported that this changing paradigm did not affect the rate of postoperative complications [14]. Our study documented a slight increase in baseline risk stratification for patients who underwent thyroid surgery after the COVID-19 lockdown, consistent with reports from China, another country hit early by the pandemic [17], though this effect was less marked in our cohort. However, short-term outcomes, evaluated as the early response to initial treatment, were not negatively impacted by the delay.…”
supporting
confidence: 88%
“…According to reports from Italy and Jordan, there was no significant difference in the oncological severity of thyroid cancer patients before and after the outbreak of COVID-19 [ 16 , 35 ]. However, a study in China reported that the poor prognostic factors of thyroid cancer, including extrathyroidal extension, multiple tumors, and lymph node metastasis, increased after the COVID-19 outbreak [ 18 ]. In a survey study conducted with clinicians majoring in thyroid disease, 87.9% were worried about delayed treatment for their patients during the pandemic [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to delayed diagnosis and treatment during the pandemic, thyroid cancer tended to progress to worse pathologic status, such as extrathyroidal extension and lymph node metastasis, even if most thyroid cancers typically exhibited indolent behavior. Currently, few studies worldwide have analyzed the changes in the oncologic features of thyroid cancer before and after the outbreak of COVID-19 [ 16 , 17 , 18 ]. Our aim was to analyze the clinical and pathologic characteristics of thyroid nodules and cancer patients before and after the outbreak of COVID-19 in a single university hospital in Incheon, Korea.…”
Section: Introductionmentioning
confidence: 99%
“…Most DTCs and MTCs are slow-growing tumors; surgical treatment can be postponed or elective. There are no significant differences in tumor size and lymph node metastasis between patients with delayed treatment ≤180 days and those without delayed treatment ( 41 ). However, a timely, safe, protective environment is recommended for patients with aggressive lymph node metastasis or suspected extrathyroidal metastasis ( 42 ).…”
Section: Therapeutic Approaches During the Covid-19 Pandemicmentioning
confidence: 99%